CHANGES IN FLARE AFTER INTRAVITREAL INJECTION OF THREE DIFFERENT ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR MEDICATIONS. Issue 3 (March 2015) - Blaha, Gregory R.; Brooks, Nneka O.; Mackel, Charles E.; Pani, Altin; Stewart, Avon P.; Price, Lori L.; Barouch, Fina C.; Chang, Jeffrey; Marx, Jeffrey L.
Abstract : Purpose: To compare the change in anterior chamber flare after intravitreal injection of the anti-vascular endothelial growth factor agents bevacizumab, aflibercept, and ranibizumab. Methods: Sixty-one eyes of 53 patients underwent intravitreal injection with anti-vascular endothelial growth factor medications for exudative age-related macular degeneration, diabetic macular edema, or retinal vein occlusion. There were a total of 26 eyes injected with bevacizumab, 14 eyes injected with aflibercept, and 21 eyes injected with ranibizumab. Anterior segment flare was measured with a laser flare meter (Kowa) before intravitreal injection and 1 day after injection. The change in flare was analyzed. Results: The mean change in flare after 1 day was +2.5 photons per millisecond in patients who received bevacizumab, 0.0 photons per millisecond for aflibercept, and −0.2 photons per millisecond for ranibizumab. There was a statistically significant difference between the 3 medications ( P = 0.006). Pairwise analysis of the change in flare showed a statistically significant difference between bevacizumab and ranibizumab ( P = 0.002). The change in flare in patients who received aflibercept was not different from that in those who received bevacizumab ( P = 0.08) or ranibizumab ( P = 0.99). Conclusion: There was a statistically significant increase in flare after bevacizumab injection compared with ranibizumab. This difference was small and is not believed to be clinically significant. There was no statistical difference in the change in flare between aflibercept and the other medications, although the number of eyes in the aflibercept group was small. Abstract : Anterior chamber flare was measured 1 day after intravitreal injection with 1 of 3 different anti-vascular endothelial growth factor medications. There was a small, but not clinically significant increase in flare after bevacizumab compared with ranibizumab.